Retrieval optimization in a warehouse with multiple input/output-points - Jan-Niklas Buckow; Marc Goerigk; Sigrid Knust (OR Spectrum, 2024)
Optimizing retrieval requests in warehouses is essential for maintaining a smooth flow of products. Most studies on warehouse retrieval optimization have considered no more than two input/output-points for product retrieval. In this paper, we study different variants of a new stacker crane scheduling problem, where pallets have to be retrieved in a warehouse with multiple input/output-points. The goal is to minimize the total travel time of the stacker crane to perform all retrievals. The problem variants we consider require determining either the pallet retrieval sequence, the assignment of pallets to input/output-points, or both. We prove NP-hardness results and identify cases that can be solved in strongly polynomial time. Additionally, we propose transformations to the traveling salesman problem, enabling the application of a vast collection of existing solution techniques. Finally, in an extensive computational study, we compare different problem variants, assess their gain of optimization, and experimentally analyze the impact of various instance parameters.
Keywords: 650; Logistics; Warehouse; Retrieval optimization; Multiple input/output-points